Shifting Religious Values in the Representation of “Jilboobs” Among Out-of-Town Students - Amanda Rahmawati (Journal of Religion, Local Politics, and Law, 2026)
The phenomenon of hijab use among Muslim female students in the modern era is experiencing increasingly complex dynamics of meaning. One form of this is the emergence of a fashion style known as “jilboobs”, namely the use of a hijab combined with tight clothing to highlight the curves of the body. This study aims to describe the form of jilboobs fashion style representation among Muslim female students who are away from home at the Faculty of Social and Political Sciences, Surabaya State University, analyze the shift in religious values reflected in this practice, and identify the social, cultural, and campus environmental factors that influence it. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation of ten informants of Muslim female students who are away from home. The shift in religious values is not interpreted as a loss of religiosity, but rather as a form of reinterpretation of religious values that is more flexible and contextual. Factors from the environment of travel, the influence of social media, campus culture, and pressure to be accepted in social circles are dominant factors in shaping this change. This study confirms that the hijab is no longer understood solely as a symbol of religious obedience, but also as an expression of social identity and lifestyle of Muslim female students in urban environments